Inborn errors of ketone body metabolism - Fukao, Toshiyuki (Henry Stewart Talks, 2007)
Ketone body metabolism, Diagnostic approach, Defects in ketogenesis, Defects in ketone body utilization (succinyl-CoA:3-ketoacid CoA transferase deficiency, mitochondrial acetoacetyl-CoA thiolase deficiency), Molecular basis of mitochondrial acetoacetyl-CoA thiolase deficiency (protein and DNA levels)
Updated at 2016/07/27